Multiwork and satisfaction with various life domains: Analysis of sex, gender, occupational and age differences - Agnieszka Lipińska-Grobelny (Nofer Institute of Occupational Medicine, 2016)
Background: Contemporary multiwork definitely changes its face, and statistics show that Poland is in the forefront of European countries in terms of the number of multiworkers. The question arises whether the provision of work for more than one employer can influence personal and professional satisfaction, and whether job satisfaction, satisfaction with marriage and satisfaction with life are differentiated by sex, gender, age and a job position. Material and Methods: The study involved 218 multiworkers and 218 monoworkers. The subjects completed the following research tools: a survey, the Satisfaction with Life Scale, the Job Description Questionnaire, the Job Affect Scale, the Scale of Masculinity and Femininity. Results: The research shows that multiwork differentiates satisfaction with organization and management. Sex, gender, age and job position affect the whole system of satisfaction dimensions, especially satisfaction with work and with life. Interaction of multiwork and age, sex, and job position differentiate satisfaction with certain aspects of job. Conclusions: The results of the study contribute to the deepening of knowledge about psychosocial functioning of multiworkers and the phenomenon of multiwork. Med Pr 2016;67(3):385-395